Sea surveys : Britain's contribution to hydrography - Edgell, John, Sir, 1880-1962.; Great Britain. Hydrographic Department; National Maritime Museum (Great Britain) (London : H. M. Stationery Off., 1965)
1. The early hydrographers -- 2. The hydrographers of the British Navy -- 3. Then and now -- 4. The work of the surveyor in war -- 5. Sea surveys, 1948-1965.
At head of title: National Maritime Museum.
Keywords: Hydrographic surveying